Youth tobacco access: trends and policy implications. Issue 4 (17th April 2014) - Gendall, Philip; Hoek, Janet; Marsh, Louise; Edwards, Richard; Healey, Benjamin
Abstract : Objective: We examined whether the supply routes via which New Zealand adolescents aged 14–15 years accessed tobacco had changed during a period of dynamic policy activity. Setting: We analysed data from seven consecutive years (2006–2012) of the New Zealand Action on Smoking and Health (ASH) Year 10 survey, a nationwide cross-sectional annual survey. Participants: All New Zealand schools teaching Year 10 students are invited to participate in the survey; school-level participation rates have ranged between 44% and 58% and more than 25 000 students have responded to the survey in each year. The results presented draw on the subsample who reported smoking when surveyed (N∼9200). The data were weighted by age, ethnicity and school socioeconomic status (SES) to remove effects of systematic over-response by New Zealand Europeans and under-response by those in lower SES groups from trend analyses. Primary and secondary outcome measures: The survey measured adolescents' main reported tobacco supply source. Results: Smoking prevalence declined significantly (8.1%) over the period examined (linear tend coefficient: −0.74; 95% CI −1.03 to −0.45, significant p<0.01). Friends showed a significant decline in relative importance as a supply source while caregivers and other sources showed a significant increase over the period examined. Conclusions: The findings show that social supply, particularly via friends, caregivers and others, such as older siblings, is a key tobacco source for adolescents; commercial supply is much less important. The findings raise questions about the additional measures needed to reduce smoking among youth. Endgame policies that make tobacco more difficult to obtain and less appealing and convenient to gift merit further investigation.